Interactive Multimedia Based on Articulate Storylines in the Topic of Plant Anatomy and Physiology - Septiana, I Gede Yudha; Wibawa, I Made Citra; Trisna, Gusti Ayu Putu Sukma (Universitas Pendidikan Ganesha, 2022)
In implementing online learning, students have difficulty understanding the concepts in the material being studied. The learning media provided only displays textual material and did not include concrete examples, and only provides students with viewing and listening activities without any interaction from students. This study aims to analyze the validity and practicality of interactive multimedia based on articulate storylines on plant anatomy and physiology in fourth grade elementary school. This research is a type of development research using the ADDIE model. The test subjects in this study were 2 material experts, 2 media experts, 2 design experts, 2 teachers, and 12 fourth-grade elementary school students. The questionnaire method was used as a data collection method with a rating scale instrument of 4. The data obtained were analyzed using the mean formula. Based on the results of the study, the average validity score of interactive learning based on an articulate storyline from the point of view of material experts was 3.90 with a very good category, from a media expert perspective of 3.93 with a very good category, and a design expert perspective of 3.88. with very good category. The average practicality score of interactive learning multimedia based on articulate storylines from the teacher's response was 3.88 in the very good category. The student response was 3.81 in the very good category. Based on the results of this analysis, interactive multimedia based on articulate storylines on the topic of plant anatomy and physiology in the fourth grade of elementary school is declared valid and practical so that it is suitable for use in learning in the fourth grade of elementary school.